COVID-19, palliative care and public health. (September 2020) - Rodin, Gary; Zimmermann, Camilla; Rodin, Danielle; al-Awamer, Ahmed; Sullivan, Richard; Chamberlain, Charlotte
Abstract: The lack of integration between public health approaches, cancer care and palliative and end-of-life care in the majority of health systems globally became strikingly evident in the context of the coronavirus disease 2019 (COVID-19) pandemic. At the same time, the collapse of the boundaries between these domains imposed by the pandemic created unique opportunities for intersectoral planning and collaboration. While the challenge of integration is not unique to oncology, the organisation of cancer care and its linkages to palliative care and to global health may allow it to be a demonstration model for how the problem of integration can be addressed. Before the pandemic, the large majority of individuals with cancer in need of palliative care in low- and middle-income countries and the poor or marginalised in high-income countries were denied access. This inequity was highlighted by the COVID-19 pandemic, as individuals in impoverished or population-dense settings with weak health systems have been more likely to become infected and to have less access to medical care and to palliative and end-of-life care. Such inequities deserve attention by government, financial institutions and decision makers in health care. However, there has been no framework in most countries for integrated decision-making that takes into account the requirements of public health, clinical medicine and palliative and end-of-life care. Integrated planning across these domains at all levels would allow for more coordinated resource allocation and better preparedness for the inevitability of future systemic threats to population health. Highlights: Integration across public health, clinical medicine and palliative care is needed. Oncology, palliative care and global health could be a demonstration model. The pandemic is a dramatic reminder of the need for such integration at all levels.